Opetussuunnitelmatutkimus keskustelunavauksia suomalaiseen kouluun ja opettajankoulutukseen - Autio, Tero; Hakala, Liisa; Kujala, Tiina (Tampere University Press, 2017)
"Curriculum Studies (opetussuunnitelmatutkimus in Finnish) comprise an international, multidisciplinary academic approach to creating discursive spaces for restructuring of the historical, theoretical and organisational complexities and interdisciplinary intertwinements present in current education and curriculum practices. While critically registering the international trends, Curriculum Studies can provide an integrative and coordinative framework for national education policy making, curriculum reforms, teachers' pre- and in-service education and the daily work of teachers. Curriculum Studies is an indispensable element in teacher education programs in order to expand the professional horizon of student teachers and make their tacit assumptions of education and teaching more explicit and articulate. The book consists of ten peer-reviewed articles, which are organised according to three main themes. The first theme, A history of Finnish curriculum theory, would render an effort to explicate and contextualise the historical trajectories embodied in today's curriculum and education theories and ideals. The two traditional master narratives, the German-Scandinavian Bildung with the Anglo-American Curriculum, have provided the contested platform for Finnish education and curriculum theories and practices. The second theme - The conflicting nature of prevailing teacher education discourses and the need for their more comprehensive and contextualised articulation - serves to juxtapose the dilemma between academic expectations and the actual working conditions of teachers. The role of teacher education is considered vital to dealing with these tensions. Another purpose of the theme is an attempt to expand and complicate the intellectual horizon of the taken-for-granted conception of the curriculum. The third theme of the book, The teacher as a curriculum theorist and curriculum maker, examines how the teacher and the school are cross-pressured by the conflicting interests of school and teacher autonomy and external supervision and evaluation. In addition, the issues of educational leadership amid the ideological tensions of the curriculum and how this complex can be engaged with the role of the teacher is scrutinised to some extent. In particular, the focal point here is the 2014 Finnish basic education curriculum reform. At best, Curriculum Studies can render the institutional education more transparent, vertically by exposing its historical trajectories and horizontally by revealing its present circumstances and political affiliations. As an academic field, the intellectual ambition of Curriculum Studies is to increasingly become aware of the normative, political and knowledge/power dynamics of education under constant negotiation with all its intended and unintended consequences. "